Significances given by future nursery school teachers to the ICT incorporated in their training process - Flores-Lueg, Carolina (2018)
Information and Communication Technologies (ICT) and its presence in education has undoubtedly given rise to important challenges to teachers, as this actor has have had the need for developing competences that allow them to incorporate these tools into their teaching practices for pedagogical purposes, aspect that must be certainly addressed by the initial training. This article presents the results of a study carried out in a chilean university whose purpose was oriented to establish the significance that students from pedagogy in nursery education attribute to the ICT incorporated in their formative process from a pedagogic perspective. It was used a qualitative approach, a case study design, with a case study design. Data and information collection was carried out through two focus group where sixteen students took part in. Both focus group were transcribed literally and later analyzed by a process of mixed coding supported by Atlas.tiv.7 software. Results show that students recognize positively the worth of ICT use in children’s education, but first, they demand to be prepared to use them, aspect which has been poorly intentioned within the training process, because students only have one subject oriented to the instrumental use of these tools in first year of studies, feeling insufficient preparation to incorporate them pedagogically into the educational process of the preschoolers. It concludes the need to incorporate ICT transversally in the training process, based on practical experiences that allow a pedagogical appropriation of them to transfer them to the classroom.